Expanding the VR for the Social Good Initiative to Brazilian Higher Education - Lima, Julia G.; Palmeira, Eduardo G.; Sardá, Gabriela C.; Feijóo-García, Pedro G.; de Siqueira, Alexandre G.; Ferreira, Marcelo G. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
This paper explores the expansion of the “VR for the Social Good” (VR4SG) initiative from the University of Florida to the Brazilian higher education context. In Brazil, the general public predominantly views Virtual Reality (VR) as just an entertainment tool, yet we intend to highlight its potential for addressing local Social Good issues. Therefore, this paper proposes a structured adaptation of the VR4SG course tailored to contextual needs, resources, implementation requirements, and desired social changes within Brazilian communities. This proposal is informed by our analysis of various versions of the course over the years, utilizing the Service Blueprint tool to outline a clear and effective strategy for implementation. Overall, the proposed expansion of the VR4SG course in the Brazilian Higher Education scenario aims to empower students from different disciplines into proactive, real problem solvers using VR technology. With this approach, we expect to inspire and qualify Brazilian students to go beyond consuming VR media to create immersive narratives capable of shifting perspectives and fostering empathy. By promoting teamwork and effective communication, the course can not only enhance personal skills but also contribute to social change, aligning with the United Nations’ Sustainable Development Goals.